Kinetic and equilibrium studies on the adsorption of reactive lack 5 dye by cross-linked chitosan/oil palm ash compostie beads / Masitah Hasan, Bassim H. Hameed and A. Latif Ahmad - Hasan, Masitah; H. Hameed, Bassim; Ahmad, A. Latif (2008)
In this study, the potential of cross-linked chitosan/oil palm ash composite beads (CLCOPA) in the removal of synthetic anionic dye reactive black 5 from aqueous solutions was investigated. Experiment was conducted in a batch system at initial dye concentration of 50-500 mg/L and temperature of 30°C. Equilibrium isotherm models, Langmuir and Freundlich were employed to describe the adsorption capacity of dye solutions. The adsorption capacity was found to be 357. 1 mg/g. The result of this analyses showed the adsorption of reactive black 5 can be successfully described by Langmuir and Freundlich equilibrium isotherm model. The adsorption kinetics of reactive black 5 onto CLCOPA were also studied to characterize of the surface complexation reaction. A pseudo-second-order mechanism has been developed to predict the rate constant of the adsorption, the equilibrium capacity and initial adsorption rate with the effect of initial concentration.